Decision Supporting System For Malang City Baseball and Softball Athletes Selection Using The Vikor Method - Eka Larasati Amalia; Deasy Sandhya Elya Ikawati; Muhammad Arya Puja Laksana (International Journal of Science, Engineering, and Information Technology, 2020)
Decision support system is a computer-based system that is used to solve problems by semi-structured and unstructured conditions. In this case, the best solution can be found from certain criteria and provided alternatives and is easy to use by users. In this study, researchers designed and built a website-based decision support system to select athletes in PERBASASI Malang with the provided test criteria, namely the hit test, catch test, throw test, and run test. The purpose of this study was to provide recommendations for participants who passed the selection based on test scores that have been processed using the VlseKriterijumska Optimizacija I Kompromisno Resenje (VIKOR) method. From the results of calculations, the use of the VIKOR method for this case study produced an accuracy value of 90.90%, a precision value of 93.33%, and a recall value of 93.33%. In addition, the VIKOR sensitivity test showed a consistent ranking of the calculation of the value with veto (value of v less than 0.5), by consensus (value of v is 0.5), and voting by majority rule (value of v more than 0.5). User testing that was applied by using each level of the existing account, i.e. administrator account level, selection account level, and members account level conducted on this information system concluded that the system that was built was running smoothly and was easy to use.